Deconstructing Self-Medication: The Dominance of Attitude and Social Norms over Perceived Control in Non-Prescription Amoxicillin Use - Maria Regina Lusiana Kya; Titien Siwi Hartayu (HM Publisher, 2025)
The global escalation of antimicrobial resistance (AMR) is profoundly exacerbated by the irrational self-medication of antibiotics. This study was conducted in the Ende Tengah District, a community within an Indonesian province where non-prescription antibiotic acquisition is highly prevalent. The primary objective was to deconstruct the psychosocial determinants of the intention to self-medicate with amoxicillin, framing the analysis within the context of a recent regulatory change designed to limit antibiotic access. A quantitative, cross-sectional study was undertaken between April and May 2025. Using a purposive sampling strategy, 109 community members aged 18-60 who had used amoxicillin without a prescription were recruited from public-access areas. Data were gathered using a structured, pilot-tested questionnaire based on the Theory of Planned Behavior (TPB), which demonstrated good internal consistency (Cronbach’s α: 0.78-0.85). The instrument measured attitude, subjective norms, perceived behavioral control (PBC), and behavioral intention. Multiple linear regression was used for the primary analysis after all statistical assumptions were confirmed. The regression model was statistically significant (F(3, 105) = 21.267, p < .001) and accounted for 37.8% of the variance in self-medication intention (R² = 0.378). Attitude emerged as the most powerful predictor of intention (β = 0.341, p = .001), followed by subjective norms (β = 0.276, p = .015). Strikingly, perceived behavioral control, the construct most related to access, was not a significant predictor of intention (β = 0.081, p = .459). In conclusion, among the study participants, the intention to self-medicate with amoxicillin is overwhelmingly a psychosocial phenomenon, driven by favorable personal attitudes and deeply ingrained social norms rather than by perceptions of access. This suggests that top-down regulatory policies focused solely on restricting antibiotic supply may be insufficient without parallel, community-focused strategies designed to reshape the beliefs and behaviors that sustain demand.